Justice Reform in Portugal: the Satisfaction of ADR Media Users - Catarino, João Ricardo; Viegas Cruz Dias, Mariana Teles; Alves Ribeiro Correia, Pedro Miguel (Revista del CLAD Reforma y Democracia, 2020)
Within the framework of the recommendations of the European Commission for the Efficiency of Justice (CEPEJ) for the reform of justice in the Member States of the Council of Europe, the Protocol of Collaboration for Monitoring the Means of Alternative Dispute Resolution (ADR) was stablished in Portugal. The objective of this article was to measure and model the ADR Means users’ satisfaction in Portugal, applying the Structural Equation Modeling (SEM) methodology to the data collected through the protocol. The scale and model proposed by Catarino and Correia (2017) for the Arbitration have been adapted here for all the ADR Means - Arbitration, Conciliation and Mediation (between October 2013 and July 2017). The results obtained have enable to revalidate the adapted scale and model, concluding that the users have been “very satisfied” with the seven dimensions of ADR Means (Information, Operation, Manager, Resources, Facilities, General Aspects and Loyalty). This work contributes to meet the recommendations of CEPEJ (2010 and 2014) and to extent the results of Catarino and Correia (2017) in a set of ADR Means and in a longer time lapse.